Efficient Use of Photovoltaic System Using Modern Control Approaches - Abu Sharkh, Ahmad; Al Salahat, Hamza; Nofal, Mohammad; Qasrawi, Mohammad (جامعة بوليتكنك فلسطين , كلية الهندسة , ميكانيك, 2017)
Under difficult political and economic circumstances which suffering by the inhabitants of Palestine and due to the compulsory controlling of power sources. In addition, expensive electricity cost compared to other countries, it is necessary to exploit solar energy as Palestine exposed to considerable hours of radiation and good solar radiation throughout the year, the period of highest efficiency of solar cells is not invested to run the devices and this was shown after measuring the power consumption of several houses , the energy generated must be stored or sold to the network; moreover, the cost of operation and establishment of photovoltaic system still expensive. After study and analysis show that harmonic problem will occur if connect PV system to the grid which is called (on-grid) system, On the other hand, storage of energy for use at the time of need is expensive because of the high price of storage batteries as well this system appellation (off-grid). In this project design, and implementation a fuzzy logic controller to control working times of some electrical appliances in the home without affecting end- user's comfort, to move the on-peak into the off-peak to reduce the number of batteries and cells used in the system and save electricitycost purchase. في ظل الظروف السياسية والاقتصادية الصعبة التي يعاني منها سكان فلسطين، والتحكم القسري بالطاقة من قبل المصدر. وبالإضافة إلى ذلك، تكلفة الكهرباء باهظة الثمن بالمقارنة مع البلدان الأخرى، فإنه من الضروري استغلال الطاقة الشمسية حيث ان فلسطين تتمتع باسقاط شمسي جيد و ساعات طويلة من الإشعاع الشمسي على مدار السنة، ان فترة أعلى كفاءة للخلايا الشمسية لا يتم استغلالها لتشغيل الأجهزة وتبين ذلك بعد قياس الاستهلاك الكهربائي لعدة منازل لذلك يمكن تخزين الطاقة المتولدة من الخلايا الشمسية أو بيعها للشبكة؛ وعلاوة على ذلك، فإن تكلفة التشغيل وإنشاء نظام الخلايا الشمسية لا يزال باهظ. بعد الدراسة والتحليل، تبين أن مشكلة عدم توافق الجهود ستحدث إذا وصل النظام بالشبكة وهذا النظام يسمى )نظام موصول بالشبكة( . من ناحية أخرى، تخزين الطاقة للاستخدام في وقت الحاجة مكلف بسبب ارتفاع أسعار بطاريات التخزين وكذلك هذا النظام يسمى )نظام غير موصول بالشبكة(. في هذا المشروع سوف يكون العمل على تصميم متحكم يقوم بالتحكم بأوقات عمل بعض الأجهزة الكهربائية في المنزل دون التأثير على راحة المستخدم ، لنقل اعلى ذروة استهلاك في المنزل الى أوقات ذروة الخلايا الشمسية من أجل تقليل عدد البطاريات والخلايا ووتوفير تكلفة شراء الكهرباء.
CD 30295 , no of pages145, ميكانيك 24/2017 , in the store
Keywords: Photovoltaic System,Data Logger,Building,MATLAB,Fuzzy